Synthesis of Novel Pyrimidin-1(2H)-ethanediamide Derivatives - Onal, Zulbiye; Ozer Ilhan, Ilhan (Asian Journal of Chemistry, 2011)
Various novel pyrimidin-1(2H)-yl-ethanediamide derivatives (2a-f) have been synthesized efficiently in good yields by the treatment of 1-aminopyrimidine-2(1H)-one/-thione derivatives (1a-f) with oxalyl dichloride. Structures of these compounds 2a-f were established on the basis of elemental analysis, IR, 1H NMR and 13C NMR spectral studies.